ANALISIS EFEKTIVITAS PENGELOLAAN PIUTANG USAHA PADA PERUSAHAAN LOGISTIK DI KABUPATEN GRESIK - Maulidiyah; Elok Vilantika (Universitas Sarjanawiyata Tamansiswa, 2025)
This study aims to analyze the effectiveness of accounts receivable management in a logistics company located in Gresik Regency. Using a qualitative case study approach, data were collected through in-depth interviews, direct observation, and document analysis involving the account receivable unit. The analysis followed the Miles and Huberman interactive model, encompassing data reduction, data display, and conclusion drawing. The findings indicate that the company has implemented relatively structured accounts receivable management procedures, including invoicing control, payment due date monitoring, aging analysis, and staged collection processes. However, despite the existence of these procedures, significant challenges remain, particularly related to long-outstanding receivables exceeding 365 days. These issues are driven by internal factors such as administrative constraints, incomplete documentation, and system migration problems, as well as external factors including customers’ financial instability. The study concludes that although receivable management practices align with theoretical standards, their effectiveness is constrained by operational and historical limitations that require further improvement